Critical review of sham surgery clinical trials: Confounding factors analysis. (December 2016) - Ciccozzi, Massimo; Menga, Rosa; Ricci, Giovanna; Vitali, Massimiliano Andrea; Angeletti, Silvia; Sirignano, Ascanio; Tambone, Vittoradolfo
Abstract: Objective: Sham surgery (placebo surgery) is an intervention that omits the step thought to be therapeutically necessary. In surgical clinical trials, sham surgery serves an analogous purpose to placebo drugs, neutralizing biases such as the placebo effect. A critical review was performed to study the statistical relevance of the clinical trials about sham surgery in the light of potential confounding factors. Materials and methods: For the critical review 52 articles were included. The possible confounding factors have been studied using a structured interpretative research form designed by the authors. This form includes the following ten confounding factors: I), lack of homogeneity among inclusion/exclusion criteria. II), false double blind. III), lack of post-surgery double blind. IV), power of the study. V), sample characteristics. VI), lost patients to Follow-up. VII), gender distribution. VIII), age equilibrium. IX), lack of psychological patient evaluation. X), lack of psychiatric patient evaluation. In most of the studies, at least one confounding factor was present. Results: The analysis of the confounding factors showed that they could influence the reliability of the surgical placebo effects. Conclusions: The validity of sham surgery should be reconsidered. Highlights: In sham surgery literature there's no assessment on confounding factors effect. Even if sham surgery has been used as control for over 30 years it isn't a standard. The validity of sham surgery is not completely supported by available literature.